Assessment of the educational experience in the Neurosurgery Residency Program of the University of Puerto Rico Medical Sciences Campus - Brau, Ricardo H.; Murray, Irina; Quiruz, Estefanía; Gelpi, Francisco; Cabrera, Fernando; Rivera, Carol; Haddock, Luis (Puerto Rico Health Sciences Journal, 2007)
Objective: In 2003, the American Council of Graduate Medical Education (ACGME) made significant changes in the medical postgraduate training policies, especially the 80 Duty Hours per Week Regulation. The Neurological Surgery Department at Mayo Clinic performed a national survey regarding the perceptions of program directors and residents on how compliance with the ACGME requirements has changed neurosurgery training. Using a similar methodology, we analyzed the University of Puerto Rico’s Medical Sciences Campus, Neurological Surgery Division’s resident and faculty staff perceptions with regard the way its training is currently performed. Methods: Anonymous questionnaires were distributed among the neurosurgery division’s resident and faculty staff at the University of Puerto Rico Medical Sciences Campus. Performance on the American Neurological Surgery Board (ANSB) written examinations was obtained from residents’ records. The quantity and types of surgeries performed by residents was retrieved from neurosurgery section computer files. The relevant data was entered into a database and descriptive analysis and frequency distributions were performed. Results: Surveys showed some concerns from both residents and attending physicians on the topics of inpatient and outpatient facilities, research activities, duty hours and the number of residents currently in the program. An upward trend in the residents’ ANSB written examination performance was observed over the years. The residents’ yearly number and diversity of surgical procedures were adequate. Conclusions: Considering the results from the surveys, the performance of residents in the Board examination, and their surgical experience, it is concluded that the general perception of the educational experience in neurosurgery is satisfactory but improvements could be made.